Effects of laser irradiation and tooth mousse on tooth hypersensitivity after office bleaching: A non-randomized clinical trial - Mohammadmahdi Sadri; Afrooz Nakhostin; Fahimeh Salamat (Wolters Kluwer Medknow Publications, 2023)
Background: This study aimed to assess the effect of laser irradiation and Tooth Mousse on tooth hypersensitivity (TH) after office bleaching (OB). Materials and Methods: This clinical trial, parallel-design split-mouth nonrandomized was conducted on 30 patients requiring OB. After scaling and fabrication of a custom tray, 35% hydrogen peroxide was applied on all teeth, and 940 nm diode laser (10 W, Class IV, 110-240 V) was irradiated to the upper and lower right quadrants. Laser in off mode was used for the left quadrants. Bleaching agent was then reapplied. After completion of bleaching, a custom tray containing tooth Mousse was placed on the maxillary arch while the tray was used without the paste for the mandibular arch. A visual analog scale was used to assess the degree of TH at 15 min and 24 h after OB. Data were compared using t-test, paired t-test, and analysis of variance. Significance level was set at α = 0.05. Results: Comparison of TH at 15 min and 24 h after OB showed a significantly lower TH score in the left upper quadrant (tooth Mousse alone) than right upper quadrant (both laser and Tooth Mousse) (P < 0.05). The TH score in the right upper quadrant was significantly lower than that in the right lower quadrant (laser only) (P < 0.05). The mean TH score in the left upper quadrant was insignificantly lower than that in the left lower quadrant (no intervention) (P > 0.05). Conclusion: The use of 940 nm diode laser for OB increases the postoperative TH. The application of Tooth Mousse can effectively decrease TH after OB with/without laser irradiation.